Philanthropic Management in Improving the Quality and Access to Education - Azizah, Yulia Luthfiyani; Putri, Febriyanti Eka (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The gap in access to education in Indonesia, especially in rural areas, still needs to be addressed with human resource development. Poverty, limited infrastructure and geographical constraints exacerbate this gap. This research examines the contribution of Lazismu as a Muhammadiyah philanthropic institution in addressing this gap through education programs. The researcher used a descriptive qualitative approach to analyze the impact of Lazismu's education programs, such as Sang Surya Scholarship, Mentari Scholarship, and Save Our School. The researcher conducted this research at the Lazismu branch of Universitas Muhammadiyah Yogyakarta. The researcher chose this research location because Lazismu Universitas Muhammadiyah Yogyakarta operates as one of the philanthropic institutions that offer educational programs. The results of the study show that the programs organized by Lazismu Universitas Muhammadiyah Yogyakarta have had a significant positive impact in increasing access to education for students from underprivileged families and improving the quality of school facilities and infrastructure in remote areas. Lazismu programs have proven effective in reducing the burden of education costs for low-income families, enabling children to stay in school, and creating a conducive learning environment